1975
DOI: 10.3181/00379727-150-38979
|View full text |Cite
|
Sign up to set email alerts
|

Water Diuresis from Clonidine (Catapres)

Abstract: Available clinical and experimental evidence indicates that clonidine 2-2(2,6-di-ch1orophenylamino)-2 imidazoline hydrochloride, has potent hypotensive, bradycardic and bradypneic properties (1-6). It also produces sedation and local anesthesia, inhibits gastric acid secretion, and raises blood sugar (7). Its effect on blood pressure in the anesthetized dog is a bimodal one. An initial short rise is followed by a prolonged decrease. Similar observations have been reported in the rabbit, rat, and cat (8,9). Con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1982
1982
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…In previous studies in dogs (either conscious or anaesthetized), the effects on sodium excretion of intravascular (either intravenous or intrarenal) administration of x2adrenoceptor agonists such as clonidine and guanabenz have ranged from antinatriuresis to natriuresis. However, these studies are difficult to interpret since in all except one (Strandhoy et al, 1983) no control experiments are reported (Marchand et al, 1971;Chrysanthakopoulos & Lavender, 1975;Olsen, 1976;Strandhoy et al, 1982). Our study clearly shows that intravenous administration of guanabenz, which is an a2-adrenoceptor agonist with very low affinity for 1,-binding sites, causes a diuresis but not a natriuresis in conscious normally-hydrated dogs, regardless of whether their autonomic reflexes are intact, or blocked by administration of pentolinium.…”
Section: Effects Of Guanabenz and Rilmenidinementioning
confidence: 99%
“…In previous studies in dogs (either conscious or anaesthetized), the effects on sodium excretion of intravascular (either intravenous or intrarenal) administration of x2adrenoceptor agonists such as clonidine and guanabenz have ranged from antinatriuresis to natriuresis. However, these studies are difficult to interpret since in all except one (Strandhoy et al, 1983) no control experiments are reported (Marchand et al, 1971;Chrysanthakopoulos & Lavender, 1975;Olsen, 1976;Strandhoy et al, 1982). Our study clearly shows that intravenous administration of guanabenz, which is an a2-adrenoceptor agonist with very low affinity for 1,-binding sites, causes a diuresis but not a natriuresis in conscious normally-hydrated dogs, regardless of whether their autonomic reflexes are intact, or blocked by administration of pentolinium.…”
Section: Effects Of Guanabenz and Rilmenidinementioning
confidence: 99%
“…The compound produced highly significant increases in the excretion of water and sodium and chloride ions, whereas the potassium excretion remained unaffected. This effect was highly reminiscent of that produced by clonidine (4) and suggestive of a lack of correlation with the compound's adrenergic receptor selectivity in anesthetized dogs. Abbott-572 19 given intravenously at doses of I to 30 pg/kg exhibited hemodynamic effects consistent with its a-adrenoceptor agonistic profile: an increase in blood pressure and a decrease in heart rate, dP/ dt,,,, and cardiac output.…”
Section: Ancillary Pharmacologymentioning
confidence: 93%
“…(2) Pharmacology [ 66 ]: Clonidine evokes increased free water clearance and urine flow in anesthetized dogs [ 282 ] and water and sodium diuresis (anti-antidiuretic hormone: ADH [ 283 , 284 , 285 ]), a large increase in urine output and the anti-inflammatory cytokine IL-10, and a lowering of the pro-inflammatory cytokine IL-6 in septic sheep [ 197 ] without changes in creatinine clearance or sodium excretion. Low dose clonidine (0.25 μg·kg −1 ·h −1 ) elicited vasodilation and increased CO (presumably increased SV) [ 197 ], a lowering of plasma renin activity, and sodium and weight loss [ 286 ] in hypertensive patients.…”
Section: Alpha-2 Agonistsmentioning
confidence: 99%